PENGARUH PARTISIPASI AGGARAN TERHADAP KINERJA MANAJERIAL MELALUI KEADILAN DISTRIBUTIF, KEADILAN PROSEDURAL, DAN KOMITMENORGANISASI SEBAGAI VARIBEL INTERVENING (studi empiris pada rumah sakit kota semarang) - Meyke Cynthia Dewi; Abdul Rohman (Diponegoro Journal of Accounting, 2016)
This study aims to examine the influence of budget participation to managerial performance. It also to examine whether perception of distribution budgetary fairness, perception of procedural budgetary fairness and organitation’s commitment mediate the relationship of budget participation and managerial performance.This study used questionnaires and interview to collecting data. From 130 questionnaires were given to managers in Diponegoro University. The questionnaires that complete the answers were 68 questionnaires. Path analysis was utilized to examine the direct and indirect effects of budget participatio to managerial performanceThe results of this study showed that budget participation has a direct effect to managerial performance. Budget participation also has a positive effect to perception of distribution budgetary fairness, perception of procedural budgetary fairness and organitatio’s commitment as intervening variables of managerial performance.